Steroids as an adjunct for reducing the incidence of proliferative vitreoretinopathy after rhegmatogenous retinal detachment surgery: a systematic review and meta-analysis - Shi H; Guo T; Liu PC; Wang QY; Du YR; Liu QY; He MM; Liu JL; Yu J (Dove Medical Press, 2015)
Hui Shi,1,2* Tao Guo,3* Peng-Cheng Liu,1 Qian-Yi Wang,1 Ya-Ru Du,1,2 Qing-Yu Liu,1 Meng-Mei He,1 Jun-Ling Liu,1 Jing Yu1 1Department of Ophthalmology, Shanghai Tenth People’s Hospital, School of Medicine, Tongji University, Shanghai, 2Department of First Clinical Medical College, Nanjing Medical University, Nanjing, Jiangsu, 3Department of Ophthalmology, Shanghai Third People’s Hospital, School of Medicine, Shanghai Jiao Tong University, Shanghai, People’s Republic of China *These authors contributed equally to this work Background: This meta-analysis was performed to determine the effectiveness of steroids as an adjunct following rhegmatogenous retinal detachment (RRD) surgery. Methods: RRD patients with or without proliferative vitreoretinopathy (PVR) were included. The treatment group included patients in whom steroids were used as an adjunct and a control group in which placebo was used. Only randomized controlled trials were included. We searched the main electronic databases and included studies published until July 2014. PVR odds ratio, visual acuity, retinal reattachment rate, and complications were evaluated in three trials. Results: Three randomized controlled trials were included in the meta-analysis. There was no significant difference in the incidence of postoperative PVR between groups (heterogeneity I2=48%, P=0.14). However, the incidence of postoperative PVR was lower in the treatment group (I2=0%, P<0.0001) than in the control group when a PVR grade C study was excluded. There was no statistically significant difference in postoperative visual acuity between the treatment and control groups (odds ratio -0.18; 95% confidence interval -0.38, 0.02; P=0.08). The two groups had similar results for primary/final retinal reattachment and reoperation rate. There was no significant difference in postoperative intraocular pressure. Conclusion: This systematic review demonstrates that steroids may significantly reduce the incidence of postoperative PVR grade B or lower following RRD surgery. Keywords: proliferative vitreoretinopathy, steroids, meta-analysis